PENGARUH BUDAYA KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI MELALUI PENILAIAN KINERJA PADA PEGAWAI KELURAHAN DI KECAMATAN WALANTAKA - Komalasari, Komalasari; Mukhlis, Ahmad; Permana, Angrian (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
The results of service performance cannot be separated from the performance of the employee himself, the better the performance assessment carried out by the leadership, the higher the employee's performance which will have an impact on the performance of the organization. This research was conducted in Walantaka Village, Walantaka District with the aim of the research, namely to determine and analyze the influence of work culture on employee performance, work discipline on employee performance, performance appraisal of employees, work culture on performance appraisal, work discipline on performance appraisal, work culture on performance through performance assessments and work discipline on performance through performance assessments of sub-district employees in Walantaka District. This research uses quantitative methods with a correlational design. The analysis method in this research uses regression with the SmartPLS statistical tool. The population of this study focused on the Subdistrict Civil Service (ASN) in Walantaka District as many as 67 employees, with sample determination using census sampling techniques so that the number of samples studied was 67 employees. The H2 test results obtained a P-value of 0.054 > 0.05 and a T-Statistics value of 1.927 < 1.96 so that Ho was accepted and Ha was rejected, the H2 test results obtained a P-value of 0.148 > 0.05 and the T-value The statistics are 1.445 < 1.96 so that H0 is accepted and Ha is rejected, the results of the H3 test show a P-value of 0.000 < 0.05 and a T-Statistic value of 16.501 > 1.96 so that H0 is rejected and Ha is accepted, the results of the H4 test are obtained The P-value is 0.014 < 0.05 and the T-Statistic value is 4.453 > 1.96 so that H0 is rejected and Ha is accepted, the results of the H5 test show a P-value of 0.000 < 0.05 and a T-Statistic value of 4.720 > 1.96 so H0 is rejected and Ha is accepted, the results of testing H6 get a P-Values ​​value of 0.014 < 0.05 and T-Statistics of 2.452 > 1.98 so H0 is rejected and Ha is accepted and the results of testing H7 get a P-Values ​​value of 0.000 < 0.05 and T-Statistics of 4.435 > 1.98 so that H0 is rejected and Ha is accepted.